2014
DOI: 10.1007/s00586-014-3615-1
|View full text |Cite
|
Sign up to set email alerts
|

Sacropelvic fixation in adult spinal deformity (ASD); a very high rate of mechanical failure

Abstract: Pelvic fixation is still associated with a very high rate of mechanical failure. Major risk factors appear to be age and type of fixation. Although could not be shown to be statistically significant, failure to restore the optimal sagittal balance may be a contributing factor as well. So in conclusion, in cases with suboptimal sagittal plane correction, S2AI with polyaxial screws seem to have higher risk of short-term acute failure compared to IwL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 15 publications
1
80
2
Order By: Relevance
“…The 5 selected studies were all retrospective cohort studies comparing outcomes of IS fixation and S2AI screw fixation techniques in adults. 5,[7][8][9]13 Based on the NASS guidelines, all studies were graded as level III evidence (retrospective comparative studies). After risk-of-bias analysis, it was found that all studies had a high risk of selection and performance bias given their nonrandomized and nonblinded nature (Fig.…”
Section: Literature Review and Study Qualitymentioning
confidence: 99%
“…The 5 selected studies were all retrospective cohort studies comparing outcomes of IS fixation and S2AI screw fixation techniques in adults. 5,[7][8][9]13 Based on the NASS guidelines, all studies were graded as level III evidence (retrospective comparative studies). After risk-of-bias analysis, it was found that all studies had a high risk of selection and performance bias given their nonrandomized and nonblinded nature (Fig.…”
Section: Literature Review and Study Qualitymentioning
confidence: 99%
“…Rigid distal fixation of the spine is essential for maintaining proper sagittal and coronal balance. Lumbosacral fusion provides a biomechanical support at the base of a long construct; however, high instrument failure and reoperation rates have been reported when S1 screws are used alone [1,2]. The L5-S junction has the highest risk of pseudoarthrosis, with a reported rate of 24% and is associated with adverse clinical outcomes [3].…”
Section: Introductionmentioning
confidence: 99%
“…The L5-S junction has the highest risk of pseudoarthrosis, with a reported rate of 24% and is associated with adverse clinical outcomes [3]. Multiple studies have shown that long instrumentation and fusion at the sacrum require supplemental pelvic fixation in order to prevent these complications [1,2]. To date, several techniques have been reported, including the use of iliac screws, S2 pedicle screws [4], sacral alar screws [5], and S2 alar-iliac (SAI) screws [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…5,6,25,48,49,[53][54][55][56][57]60 However, these procedures are often complex and may be associated with high rates of complications. 4,6,14,15,17,22,39,44,45,[50][51][52]55,58,61,63 Previously reported studies of ASD surgery complications have been limited by retrospective design, single-surgeon or single-center cohorts, lack of rigorous data on complications, and/or limited follow-up. Improved understanding of the types of complications and their rates of occurrence with ASD surgery, both during the perioperative period and over the course of follow-up, is important for treatment planning, patient counseling, and ongoing efforts to improve the safety of care.…”
mentioning
confidence: 99%